Comparative Analysis of The Process of Resolving Labor Disputes in The Russian Federation and The Republic of Indonesia - Gratio, Roberto Bellarmino (Jurnal Multidisiplin Indonesia, 2025)
This research is motivated by the similarities in socio-economic conditions related to employment and the need for adequate labor law, particularly in resolving industrial relations disputes in both the Russian Federation and the Republic of Indonesia. This research further identifies various aspects of similarities and differences in labor dispute resolution in Indonesia. the purpose of the work is to study and comprehensively and comparably analyze, based on the theory, empirical material and judicial practice, the norms of labor legislation for the resolution of labor disputes in the Russian Federation and the Republic of Indonesia.The object of the research is the methods and mechanisms of the process of settlement of labor disputes used in the Russian Federation and the Republic of Indonesia while the subject of the research is the system of labor law norms that regulate the methods and mechanisms of the process of resolving labor disputes in the Russian Federation and the Republic of Indonesia. The results of this study are a comprehensive, qualitative analysis of the labor dispute resolution systems in both the Republic of Indonesia and the Russian Federation, encompassing existing laws and regulations, legal institutions, and labor dispute resolution procedures. It is hoped that this research can serve as constructive evaluation material for each country concerned, allowing them to review and improve their established labor dispute resolution systems.